Effects of traditional music therapy on the psycho-neuro-immuno-endocrine aspect of burnout syndrome in healthcare workers: A randomized controlled trial - Ardani, Yanuar; Shatri, Hamzah; Koesnoe, Sukamto; Yunir, Em; Wiguna, Tjhin; Wibowo, Heri; Sawitri, Dian R.; Sarwono, Sugeng J.; Masyur, Muhtaruddin; Ricardo, William; Katarina, Matilda; Anggono, Rendi F. (Narra Sains Indonesia, 2025)
Burnout syndrome (BOS) is an occupational phenomenon highly prevalent among healthcare workers, particularly physicians and nurses. Despite its prevalence, no single therapy universally addresses all cases of BOS. The aim of this study was to develop a novel approach to managing BOS through traditional music therapy, evaluated from psychosomatic, neurological, immunological, and endocrine perspectives. The study involved 80 participants who were randomly assigned to either the intervention or control group. The intervention group received traditional music therapy for 10–15 minutes, three times a week, over four weeks. Key outcomes were assessed at weeks 2 and 4. Measurements included the Maslach Burnout Inventory (MBI), heart rate variability (HRV), saliva cortisol, saliva β-endorphin, saliva immunoglobulin A (IgA), and serum FOXP3. Instruments included the MBI-HSS questionnaire and HRV measuring devices. Over four weeks, significant improvements were observed in the MBI scores (p=0.001), HRV (p=0.001), and FOXP3 delta (p=0.035) in the intervention group compared to the control group. However, no significant differences were found for cortisol, β-endorphin, or IgA. These findings suggest that traditional music therapy positively impacts the psychological, neurological, and immunological aspects of BOS and potentially influences immunological and endocrine responses. Future research should explore the effects of longer intervention durations, test varying doses, and examine the combination of music therapy with other non-pharmacological treatments to enhance its therapeutic potential.